A collaborative example between archives and Wikipedia community. A Wikimedian in residence at Central Institute for Archives - Marco Chemello (JLIS.it, 2018)
The Central Institute for Archives (ICAR) and Wikimedia Italia conducted a collaboration project between September 2017 and March 2018 with the help of a Wikipedian in Residence. The project has opened a new phase of collaboration between Wikipedia and the world of Italian archives, experimenting how archives can contribute to the free encyclopedia most consulted in the world, enhancing and reaffirming the importance of their role in the digital age. Addressing the challenges that this type of project involves means facing the obstacles and resistance still present in the spread of Open Access in Italy, first of all bureaucratic, but mainly due to the mentality of institutions and archivists who, despite the evolution of the regulatory framework, seem to have rarely focused the change of paradigm which could guarantee their meaningful survival in the new millennium. The ability to exploit the paradigms of Open Access can be one of the decisive factors.